Weighted EHR-based prevalence estimates for hypertension at the state and local levels in Louisiana - Wenjun Li; Meng Zhang; Jie Cheng; Sandra L. Jackson; Adam S. Vaughan; Michael Klompas; Thomas W. Carton; Elizabeth Nauman; Lee Mendoza; Arun Adhikari; Jeanie Donovan; Katherine H. Hohman (BMC Public Health)
Abstract Background Modernization of public health data systems is a national priority. Improved chronic disease surveillance can provide more timely, accurate, and local measures to inform public health policy and intervention. Although electronic health record (EHR) data have great potential for surveillance, population coverage is non-random, which may result in biased estimates. Statistical approaches are needed to adjust estimates to represent the underlying population and validate the results against independent estimates. Methods MENDS, the Multi-State-EHR-Based Network for Disease Surveillance, uses EHR data to calculate chronic disease and risk factor prevalence metrics. In this study, we applied post-stratification weighting to MENDS data from nearly 800,000 adults from Louisiana to estimate the prevalence of hypertension and hypertension control at the state and parish (county-equivalent) levels during February 2023. We then compared weighted MENDS hypertension prevalence estimates with measures derived from traditional public health surveillance. Results Weighted MENDS hypertension prevalence estimates were approximately 10% lower than crude MENDS estimates, and approximately 13% higher than hypertension awareness estimates from the 2021 Behavioral Risk Factor Surveillance System, with similar geographic and demographic patterns. Weighted MENDS hypertension prevalence estimates indicated that 43.0% of Louisiana adult residents had hypertension (versus 47.7% crude prevalence). Prevalence was higher than the overall state estimate among men (47.3% weighted; 55.9% crude), Black patients (50.2% weighted; 55.7% crude), those receiving Medicare (70.6% weighted; 76.2% crude), and individuals living in rural areas (46.1% weighted; 49.8% crude). Hypertension prevalence increased with age and with more clinical visits during the previous 2 years. Hypertension prevalence was highest in the southeastern parishes near New Orleans and Baton Rouge. Demographic and geographic patterns in prevalence of hypertension control were like hypertension prevalence. Conclusions Post-stratification weighting of MENDS data brought EHR-based data estimates closer to survey-based estimates of hypertension and can improve representativeness of chronic disease indicators. These estimates can provide public health organizations with timely, accurate, and local information. Further, EHR-based systems can produce unique measures, such as the prevalence of hypertension control, which can provide a more nuanced understanding of community needs and help public health agencies evaluate the effectiveness of community interventions.